1996
DOI: 10.1021/ja9616342
|View full text |Cite
|
Sign up to set email alerts
|

The Prototypical Organophosphorus Ylidion CH2PH3+

Abstract: The reactivity of the prototypical phosphorus-containing ylidion (α-distonic ion) •CH2PH3 + has been investigated in the gas phase by using a dual cell Fourier-transform ion cyclotron resonance mass spectrometer. The ion •CH2PH3 + and its more stable conventional isomer CH3PH2 •+ show distinctly different reactivities toward neutral reagents. This observation contrasts the facile interconversion of the analogous sulfur- and oxygen-containing distonic ions •CH2SH2 + and •CH2OH2 + with their conventional isomers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The most important result is perhaps the fact that both the doublet and quartet PES's are well separated from each other. As observed by Radom et al, on the doublet PES, the conventional isomer CH 3 SH + ( 1 ) was found to be energetically more stable than the ylide ion ( 2 ) by 21.9 kcal/mol. The ylide ion has two C s structures which are energetically close to each other (0.2 kJ mol -1 ) with the anti conformation being more favored over the syn.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The most important result is perhaps the fact that both the doublet and quartet PES's are well separated from each other. As observed by Radom et al, on the doublet PES, the conventional isomer CH 3 SH + ( 1 ) was found to be energetically more stable than the ylide ion ( 2 ) by 21.9 kcal/mol. The ylide ion has two C s structures which are energetically close to each other (0.2 kJ mol -1 ) with the anti conformation being more favored over the syn.…”
Section: Resultsmentioning
confidence: 52%
“…For this reason, we choose the same level of theory for the full characterization of the various PES's of (CH n S) + ( n = 1−4) ions. The experimental investigations and most of the theoretical studies , on CH 4 S + are restricted largely to thermochemical data. Radom et al, 20c,d in their earlier investigation on the doublet potential energy surface of the CH 4 S + system at the MP3/6-31G**//6-31G* level, have identified transition states for three reaction channels viz., CH 3 SH + → CH 2 SH 2 + , CH 3 SH + → CH 2 SH + + H • , and CH 2 SH 2 + → CH 2 SH + + H • .…”
Section: Experimental and Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the aromatic distonic ions N..(3-dehydrophenyl)-3 -fluoropyridinium ion (Figure Ia) and 4-dehydrophenyldimethyl sulfonium ion react with CH 3SeSeCH3 by CH 3Se ' abstraction approximately three times faster than they react with CH 3SSCH3 (the reaction efficiencies are 25 and 14% versus 7 and 5%, respectively; Table 1). Similarly, the prototypical organophosphorus distonic ion 'CH z PH j reacts with CH 3SeSeCH3 by exclusive CH 3Se' abstraction at 75% of the collision rate (Figure 1c; Table 1), whereas the reaction with CH 3SSCH3 yields both the electron transfer and CH 3S ' abstraction products (at 40% of the collision rate) [13].…”
Section: Reactivitymentioning
confidence: 95%
“…The facile CH 3Se ' abstraction observed for distonic ions can be used to distinguish them from their conventional isomers. For example, while the ion 'CH zPH j reacts with CH 3SeSeCH3 by CH 3Se' abstraction, its conventional isomer CH 3PHi" yields only the electron transfer product (Table 2) [13]. Similarly, electron transfer is the only reaction observed for the conventional radical cation of trimethylene oxide, while its ring-opened distonic form 'CH zCH zOCH~yields several products, including that formed by CH 3Se ' abstraction (Tables 1 and 2).…”
Section: Reactivitymentioning
confidence: 97%